Mapping 3D fault geometry in earthquakes using high‐resolution topography: Examples from the 2010 El Mayor‐Cucapah (Mexico) and 2013 Balochistan (Pakistan) earthquakes. Issue 7 (4th April 2016) - Zhou, Yu; Walker, Richard T.; Elliott, John R.; Parsons, Barry
Abstract: Fault dips are usually measured from outcrops in the field or inferred through geodetic or seismological modeling. Here we apply the classic structural geology approach of calculating dip from a fault's 3‐D surface trace using recent, high‐resolution topography. A test study applied to the 2010 El Mayor‐Cucapah earthquake shows very good agreement between our results and those previously determined from field measurements. To obtain a reliable estimate, a fault segment ≥120 m long with a topographic variation ≥15 m is suggested. We then applied this method to the 2013 Balochistan earthquake, getting dips similar to previous estimates. Our dip estimates show a switch from north to south dipping at the southern end of the main trace, which appears to be a response to local extension within a stepover. We suggest that this previously unidentified geometrical complexity may act as the endpoint of earthquake ruptures for the southern end of the Hoshab fault. Key Points: High‐resolution topography provides a new means of mapping 3‐D fault geometry The proposed method is complimentary to the field measurements of fault dip From the fault geometry, we find variations in dip at the endpoint of the Hoshab rupture